Pharmacodynamic studies of voriconazole: informing the clinical management of invasive fungal infections. Issue 8 (2nd August 2016) - Job, Kathleen M.; Olson, Jared; Stockmann, Chris; Constance, Jonathan E.; Enioutina, Elena Y.; Rower, Joseph E.; Linakis, Matthew W.; Balch, Alfred H.; Yu, Tian; Liu, Xiaoxi; Thorell, Emily A.; Sherwin, Catherine M. T.
ABSTRACT: Introduction : Voriconazole is a broad-spectrum antifungal agent commonly used to treat invasive fungal infections (IFI), including aspergillosis, candidiasis, Scedosporium infection, and Fusarium infection. IFI often occur in immunocompromised patients, leading to increased morbidity and mortality. Areas covered : The objective of this review is to summarize the pharmacodynamic properties of voriconazole and to provide considerations for potential optimal dosing strategies. Studies have demonstrated superior clinical response when an AUC/MIC >25 or Cmin /MIC >1 is attained in adult patients, correlating to a trough concentration range as narrow as 2–4.5 mg/L; however, these targets are poorly established in the pediatric population. Topics in this discussion include voriconazole use in multiple age groups, predisposing patient factors for IFI, and considerations for clinicians managing IFI. Expert commentary : The relationship between voriconazole dosing and exposure is not well defined due to the large inter- and intra-subject variability. Development of comprehensive decision support tools for individualizing dosing, particularly in children who require higher dosing, will help to increase the probability of achieving therapeutic efficacy and decrease sub-therapeutic dosing and adverse events.